MOLECULAR STUDY AND PHYLOGENY OF Babesia spp. IN NATIVE SHEEP FROM SULAIMANI GOVENORATE/ NORTHERN IRAQ - Abdullah, Sh. H.; Ali, Sh. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to investigate Babesia parasites infecting sheep in eight districts of Sulaimani governorate/north Iraq from April to October 2017. Forty flocks of small ruminants were selected to collect blood samples randomly from 450 sheep. The samples were examined for babesiosis by microscopic examination and PCR. Primers based on the 18S rRNA were used for Babesia diagnosis, followed by sequencing of the amplicons for confirmation of the PCR product identities. Seventy-four samples (16.44%) showed the presence of Babesia piroplasms microscopically, while 116 (25.78%) samples were positive using PCR. Results showed that B. ovis was reported in 15.78% (n = 71), and B. motasi in 10.0% (n = 45) of the samples. Also, BLAST analysis of the obtained partial sequences of the 18S rRNA gene from current study isolates revealed the existence of both B. ovis and B. motasi, with a high homology degree of nucleotide identity with other nucleotide sequences of Babesia spp. in GenBank database. Distribution of babesiosis, according to the sampling time, revealed that high-frequency rates occur during July and August. Based on the result data, babesiosis was mainly caused by B. ovis and B. motasi.